Covid -19 and Cardiovascular Assessment in Critically Ill Patients: A Multidisciplinary Experience Report - S, Cipani; V, Bartolini; M, Berardinelli; M, Pazzi; C, Stera; C, Ciapetti; L, Renieri; V, Pavoni (Cardiology and Cardiovascular Medicine, 2020)
Since its recognition in december 2019, Covid 19 has rapidly spread all over the world with a global pandemic . This virus invades cells through the angiotensin converting enzyme 2 (ACE 2) receptor, particularly developed in hypertensive, atherosclerotic and congestive heart failure patients. This observation suggest that patients with pre existing cardiovascular diseases are prone to more severe complications of Covid 19 with increased mortality. To date early reports indicate two possible patterns of myocardial injury with Covid 19. We summarize our clinical experience with 30 patients hospitalized in our ICU during march and april 2020.